Cross-sectional associations between dietary intake and carotid intima media thickness in type 2 diabetes: baseline data from a randomised trial. Issue 3 (22nd March 2017) - Chiavaroli, Laura; Mirrahimi, Arash; Ireland, Christopher; Mitchell, Sandra; Sahye-Pudaruth, Sandhya; Coveney, Judy; Olowoyeye, Omodele; Patel, Darshna; de Souza, Russell J; Augustin, Livia S A; Bashyam, Balachandran; Pichika, Sathish Chandra; et al.
Abstract : Objective: To assess associations between dietary intake and carotid intima media thickness (CIMT) by carotid ultrasound (CUS), a surrogate marker of cardiovascular disease (CVD) risk, in those with type 2 diabetes. Design: Cross-sectional analysis of baseline data from 325 participants from three randomised controlled trials collected in the same way. Setting: Risk Factor Modification Centre, St. Michael's Hospital, Toronto, Canada. Participants: 325 participants with type 2 diabetes, taking oral antidiabetic agents, with an HbA1c between 6.5% and 8.0% at screening, without a recent cardiovascular event. Main outcome measures: CIMT by CUS and associations with dietary intake from 7-day food records, as well as anthropometric measures and fasting serum samples. Results: CIMT was significantly inversely associated with dietary pulse intake (β=−0.019, p=0.009), available carbohydrate (β=−0.004, p=0.008), glycaemic load (β=−0.001, p=0.007) and starch (β=−0.126, p=0.010), and directly associated with total (β=0.004, p=0.028) and saturated (β=0.012, p=0.006) fat intake in multivariate regression models adjusted for age, smoking, previous CVD event, blood pressure medication, antidiabetic medication and ultrasonographer. Conclusions: Lower CIMT was significantly associated with greater consumption of dietary pulses and carbohydrates and lower total and saturated fat intake, suggesting a potential role for diet in CVD risk management in type 2 diabetes. Randomised controlled trials are anticipated to explore these associations further. Trial registration number: NCT01063374.